Boundary Between Amorphously and Molecularly Dispersed Curcumin of Its Amorphous Solid Dispersions Determined by Fluorescence Spectroscopy - Shixin Fan; Wenling Zheng; Shizhao Ren; Wangchuan Xiao; Fenghua Chen; Rongrong Xue (Crystals, 2025)
Amorphous solid dispersion (ASD) technology is popularly used for enhancing the solubility of poorly water-soluble drugs. Drug molecules in ASDs can be dispersed in the form of either amorphous (AASD) or molecular (MASD) forms. The boundary between AASDs and MASDs (A–M boundary) is defined as the drug concentration at which the existence of MASDs obviously influences the physicochemical properties of ASDs. In this work, fluorescence spectroscopy based on the aggregation-caused quenching (ACQ) phenomenon was used to determine the A–M boundary of curcumin (CUR) ASDs prepared via neat ball milling. The relationship between the fluorescence intensity and the loading of CUR in the sample is consistent with the Stern–Volmer equation. For the CUR ASDs with PVP, the samples with CUR loading below 10% show significantly increased fluorescence and have a higher solubility (~178 μg·mL−1), suggesting the A–M boundary is around 10%. Similar A–M boundaries around 10% were also observed for CUR ASDs with PVPVA, Soluplus, HPMC, and HPMCAS. It is of great significance to define the A–M boundary of ASDs for guiding pharmaceutical ASD formulas by balancing drug loading, stability, and solubility.